Impact of liver disease on oral anticoagulant prescription and major adverse events in patients with atrial fibrillation: analysis from a population-based cohort study. Issue Volume 7:Issue FI1(2021) (4th March 2020) - Proietti, Marco; Marzona, Irene; Vannini, Tommaso; Colacioppo, Pierluca; Tettamanti, Mauro; Foresta, Andreana; Fortino, Ida; Merlino, Luca; Lip, Gregory Y H; Roncaglioni, Maria Carla
Abstract: Aims : Data on the impact of liver disease (LD) in patients with atrial fibrillation (AF) and the role of oral anticoagulant (OAC) drugs for stroke prevention are limited. Methods and results : A retrospective observational population-based cohort study on the administrative health databases of Lombardy region Italy. All AF patients ≥40 years admitted to hospital from 2000 to 2018 were considered. Atrial fibrillation and LD diagnosis were established using ICD9-CM codes. Use of OAC was determined with Anatomical Therapeutic Chemical codes. Primary study outcomes were stroke, major bleeding, and all-cause death. Among 393 507 AF patients, 16 168 (4.1%) had concomitant LD. Liver disease AF patients were significantly less treated with OAC. Concomitant LD was associated with an increased risk in all the study outcomes [hazard ratio (HR): 1.18, 95% confidence interval (CI): 1.11–1.25 for stroke; HR: 1.57, 95% CI: 1.47–1.66 for major bleeding; HR: 1.41, 95% CI: 1.39–1.44 for all-cause death]. Use of OAC in patients with AF and LD resulted in a reduction in stroke (HR: 0.80, 95% CI: 0.70–0.92), major bleeding (HR: 0.86, 95% CI: 0.74–0.99), and all-cause death (HR: 0.77, 95% CI: 0.73–0.80), with similar results according to subgroups. A net clinical benefit (NCB) analysis suggested a positive benefit/risk ratio in using OAC in AF patients with LD (NCB: 0.408, 95% CI: 0.375–0.472). Conclusion: In AF patients, concomitant LD carries a significantly higher risk for all clinical outcomes. Use of OAC in AF patients with LD was associated with a significant favourable benefit/risk ratio, even in high-risk patient subgroups.